A community effort to track commercial single-cell and spatial 'omic technologies and business trends - De Jonghe, J; Opzoomer, JW; Vilas-Zornoza, A; Crane, P; Nilges, BS; Vicari, M; Lee, H; Lara-Astiaso, D; Gross, T; Morf, J; Schneider, K; Cudini, J; et al. (Springer Nature, 2024)
There is an ever-growing choice of single-cell and spatial ’omics platforms for industry and academia. The scTrends Consortium provides a brief historical overview of the established platforms and companies, revealing market trends and presenting possible angles for how technologies may differentiate themselves.